All Days 2000
DOI: 10.2118/58785-ms
|View full text |Cite
|
Sign up to set email alerts
|

Near Wellbore Cleanup in Openhole Horizontal Sand Control Completions: Laboratory Experiments

Abstract: Wellbore cleanup in horizontal, open hole sand control completions has been the subject of many publications in recent years. Although a large majority of horizontal wells have been standalone screen completions, an increasing number of these wells are being gravel-packed, particularly in deep water, sub sea environment where reliability of the sand face completion is of utmost importance due to prohibitively high cost of intervention. In such wells, increased significance of "doing it right the first time" fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Although this breaker system gave equivalent results to those obtained with oil-based RDF systems that will be discussed shortly, it induced complete losses after ~ 6 hours, which introduces high risk of complete losses while water-packing and thus a premature screen-out yielding incomplete packing, particularly considering the additional risk of cake erosion and thus significantly lower time period for inducing high losses as discussed in the literature. 16 An alternative approach would be to use a circulation tool that would allow spotting of the same CAS/Enzyme cake cleanup treatment immediately after waterpacking. 17 However, this approach was eliminated once the decision to gravel pack with the alternate path technique has been made due to much higher success ratio compared to water-packs.…”
Section: Drilling and Gravel Packing Fluid Selectionmentioning
confidence: 99%
“…Although this breaker system gave equivalent results to those obtained with oil-based RDF systems that will be discussed shortly, it induced complete losses after ~ 6 hours, which introduces high risk of complete losses while water-packing and thus a premature screen-out yielding incomplete packing, particularly considering the additional risk of cake erosion and thus significantly lower time period for inducing high losses as discussed in the literature. 16 An alternative approach would be to use a circulation tool that would allow spotting of the same CAS/Enzyme cake cleanup treatment immediately after waterpacking. 17 However, this approach was eliminated once the decision to gravel pack with the alternate path technique has been made due to much higher success ratio compared to water-packs.…”
Section: Drilling and Gravel Packing Fluid Selectionmentioning
confidence: 99%
“…It has been demonstrated, through laboratory experiments, that cake removal during gravel packing with water is a risk that is not worth taking if a modified work string that allows circulation immediately after gravel packing is used. 31 Recent work by Brady et al 32 has shown that gravel packed wells require an enzyme or an oxidiser treatment as a minimum depending on the mineralogy (clays, clean sand etc.) along the horizontal well and gravel size, as also shown by Hodge and Burton.…”
Section: What To Do Before and After Installing Screensmentioning
confidence: 99%
“…Subsequently, a filtercake was formed on the core at 300-psi overbalance at either 170 or 200 o F over a 16-hour time period, with the reversible S/OB-RDF using a modified HPHT static fluid loss cell. 5 After 16-hours of filtration, the excess RDF was poured out of the cell. Then, a gravel slurry with the S/OB carrier fluid incorporating a pH-modifier/CaCO 3 -dissolver (CAS) was placed on top of the filtercake, with some excess carrier fluid left above the gravel pack to simulate the fluid left in the base pipe at the end of gravel-packing.…”
Section: S/ob Gravel-pack Carrier Fluid With Breakermentioning
confidence: 99%
“…This is consistent with the results reported by Brady et al for water-based-RDF filtercakes. 5 In order to investigate the effect of temperature on breakthrough kinetics, two tests were run at identical conditions, one at 170 and the other at 200 o F. As seen in Figure 4, the breakthrough time of ~ 90 minutes at 200 o F is about a factor of 3 shorter than that at 170 o F. Depending on the length of the interval to be gravel-packed, CAS systems with higher pH may be needed at elevated temperatures.…”
Section: S/ob Gravel-pack Carrier Fluid With Breakermentioning
confidence: 99%